Homogenization of the heat equation with random convolutional potential - Mengmeng Wang; Dong Su; Wei Wang (AIMS Mathematics, 2024)
This paper derived the homogenization of the heat equation with random convolutional potential. By Tartar's method of oscillating test function, the solution of the heat equation with random convolutional potential was shown to converge in distribution to the solution of the effective equation with determined convolutional potential.